2017
DOI: 10.1093/brain/awx069
|View full text |Cite
|
Sign up to set email alerts
|

Recessive dystrophic epidermolysis bullosa results in painful small fibre neuropathy

Abstract: Recessive dystrophic epidermolysis bullosa is a painful condition characterised by repeated blistering of the skin. Von Bischhoffshausen et al. report that in this condition, small sensory fibres in the skin are injured leading to neuropathic pain. These findings support the use of neuropathic pain treatment in recessive dystrophic epidermolysis bullosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Recently RDEB was described to include neuropathic pain qualities, further quantified by intraepidermal nerve fibre density (IENFD) testing (7). In our study, RDEB and JEB reported similar mean scores for pathognomonic terms, indicating neuropathic pain (hot, shooting, tingling, electrical and cold).…”
Section: Table I Definitions Of Time Qualities Of Pain As Described supporting
confidence: 54%
See 1 more Smart Citation
“…Recently RDEB was described to include neuropathic pain qualities, further quantified by intraepidermal nerve fibre density (IENFD) testing (7). In our study, RDEB and JEB reported similar mean scores for pathognomonic terms, indicating neuropathic pain (hot, shooting, tingling, electrical and cold).…”
Section: Table I Definitions Of Time Qualities Of Pain As Described supporting
confidence: 54%
“…Pain associated with extensive wounds has neuropathic qualities as it has a "burning" sensation. A recent study confirmed a source of neuropathic pain as they showed a decreased intraepidermal nerve fibre density in patients with recessive dystrophic EB (RDEB), caused by injury (probably due to trauma, metabolic-toxins, infections and nutritional deficits, amongst others) to the distal terminals of small fibres (7).…”
mentioning
confidence: 89%
“… De Kruijf et al (2016) reported a small reduction in cold detection sensitivity in those with black skin. In our experience, in a control Indian population (unpublished data) or mixed South American population ( von Bischhoffshausen et al , 2017 ) there was either no, or only minor (only in mechanical pain sensitivity) differences, respectively, in comparison to the DFNS control cohort. We do not feel, therefore, that such ethnic differences would be responsible for the large changes that we observed on QST.…”
Section: Discussionmentioning
confidence: 61%
“…The persistent inflammatory condition in RDEB skin may also contribute to central sensitization to painful stimuli, which is challenging to objectify through diagnostic techniques, and does not respond adequately to targeted therapies . The different aetiologies of pain in EB require tailored interventions and therefore pain care is optimized through combined drug treatments and psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Pain in EB significantly impacts quality of life and day‐to‐day functioning . In addition to nociceptive pain associated with blistering and wounds, peripheral nerve damage objectified in RDEB, and postulated in JEB, adds plausibility to reported high pain scores in these EB types . Neuropathies limit the central role of opioids for EB pain as they may be less effective for this type of pain according to systematic analysis …”
Section: Discussionmentioning
confidence: 99%